INDONESIAN EFL STUDENTS' ANXIETY IN WRITING FINAL PAPERS IN THE UNISKA-KEDIRI ENGLISH EDUCATION DEPARTMENT: FACTORS AND STRATEGIES - Andhika Kasim, Michael; Wulandari , Sri; Prasongko, Angga (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2024)
This article delves into the phenomenon of thesis-related anxiety among eighth-semester students at Kadiri Islamic University in Indonesia in writing final project. It highlights anxiety as a notable psychological barrier that impedes effective thesis writing. The research investigates the factors contributing to this anxiety, including fear of negative evaluation, time pressure, language difficulties, and more. The research methodology encompasses a descriptive quantitative approach involving various stages, such as preliminary research, instrument development, validation, data collection, analysis, and conclusion. Through questionnaires and data analysis, the most prevalent anxiety factors are identified. Furthermore, the article explores the strategies students employ to mitigate thesis-related anxiety. The study identifies preparation, relaxation, positive thinking, and resignation as the main coping mechanisms. By analyzing the scores of the questionnaire responses, the article reveals the most commonly adopted strategies. Notably, preparation emerges as the primary strategy, followed by resignation, positive thinking, peer seeking, and relaxation. This article contributes to the understanding of the emotional and psychological aspects of academic writing and provides valuable information for educators and institutions seeking to support students during this critical phase of their academic journey.